2021
DOI: 10.3389/fpsyg.2021.767395
|View full text |Cite
|
Sign up to set email alerts
|

“Like a Freshman Who Didn’t Get a Freshman Orientation”: How Transfer Student Capital, Social Support, and Self-Efficacy Intertwine in the Transfer Student Experience

Abstract: Community colleges and other open-access two-year campuses provide an important pathway to higher education; however, a surprisingly small proportion of these students successfully transfer to and graduate from a bachelor’s degree-granting institution. The present study examined barriers and challenges students faced as they built their sense of self-efficacy as transfer students. We conducted interviews with 65 prospective or recent transfer students, including “internal” transfers (moving from an open-access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 93 publications
(111 reference statements)
0
0
0
Order By: Relevance
“…Transfer student capital was cited as developing from many different types of sources. Students may develop transfer student capital through peers, family, student and institutional culture, high school teachers and staff, community college faculty and staff, and four-year institution faculty, staff, and advisors [27], [33], [48]. Interestingly, in one study, a latent class analysis found that race and ethnicity were not significant factors in determining transfer student capital [35].…”
Section: Strategic Focus Areasmentioning
confidence: 97%
See 4 more Smart Citations
“…Transfer student capital was cited as developing from many different types of sources. Students may develop transfer student capital through peers, family, student and institutional culture, high school teachers and staff, community college faculty and staff, and four-year institution faculty, staff, and advisors [27], [33], [48]. Interestingly, in one study, a latent class analysis found that race and ethnicity were not significant factors in determining transfer student capital [35].…”
Section: Strategic Focus Areasmentioning
confidence: 97%
“…The original presentation of transfer student capital was comprised of three theoretical frameworks: Pascarella's [30] model of student learning and development, Becker's [31] theory of human capital, and the notion of transfer student as student retention [32]. Many articles cite these three primary frameworks [22], [33], [34]. However, a variety of research studies integrate new frameworks or use existing frameworks to describe the original frameworks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations